Principle anthropocentrism in the context of modern understanding of the law - Подковенко, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article analyzes the meaning and significance of the principle of anthropocentrism in the context of modern understanding of the law. Focuses on the special purpose of law in the life of every individual and society as a whole.